2011
DOI: 10.4161/psb.6.11.17587
|View full text |Cite
|
Sign up to set email alerts
|

Role of the iron transporter OsNRAMP1 in cadmium uptake and accumulation in rice

Abstract: T he heavy metal cadmium (Cd) is toxic to humans, and its accumulation in rice grains is a major agricultural problem. Rice has seven putative metal transporter NRAMP genes, but microarray analysis showed that only OsNRAMP1 is highly upregulated by iron (Fe) deficiency. OsNRAMP1 localized to the plasma membrane and transported Cd as well as Fe. OsNRAMP1 expression was observed mainly in roots and was higher in the roots of a high-Cdaccumulating cultivar (Habataki) than in those of a low-Cd-accumulating cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(77 citation statements)
references
References 23 publications
3
73
0
1
Order By: Relevance
“…The barley cDNA sequences homologs to OsIDEF1, OsIDEF2, OsIRO2 and OsIRO3 rice genes involved in the regulation of Fe deficiency responses (Kobayashi et al , Ogo et al , , Zheng et al ) were identified by a blast search of the NCBI database using the four available rice sequences (accession numbers BR000654, AK099540, FAA00382 and AK061515). Furthermore, a blast search against the NCBI database using the seven Nramp gene sequences present in rice (accession numbers in Takahashi et al ) allowed the identification of three barley full‐length cDNAs homologs to OsNramp2, OsNramp5 and OsNramp7 genes. For the seven cDNA sequences identified by the database search specific primers were designed to amplify fragments within the 3′ end region of each sequence (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…The barley cDNA sequences homologs to OsIDEF1, OsIDEF2, OsIRO2 and OsIRO3 rice genes involved in the regulation of Fe deficiency responses (Kobayashi et al , Ogo et al , , Zheng et al ) were identified by a blast search of the NCBI database using the four available rice sequences (accession numbers BR000654, AK099540, FAA00382 and AK061515). Furthermore, a blast search against the NCBI database using the seven Nramp gene sequences present in rice (accession numbers in Takahashi et al ) allowed the identification of three barley full‐length cDNAs homologs to OsNramp2, OsNramp5 and OsNramp7 genes. For the seven cDNA sequences identified by the database search specific primers were designed to amplify fragments within the 3′ end region of each sequence (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Positive effects of priming in plant resistance have been demonstrated for different crop plants such as wheat (Iqbal & Ashraf, 2007), sunflower (Kaya et al 2006), chickpea (Kaur et al, 2002) and maize (Karalija & Selović, 2018). It is considered that cadmium is transported through membrane transport systems into the plant cells (Takahashi et al, 2011) with likely involvement of zinc and calcium transporters in the Cd transport itself (Manohar et al, 2011;Zorrig et al, 2011). Entrance of cadmium into the plant cells triggers a wide range of toxic effects on photosynthesis through decrease in chlorophyll concentrations, induction of oxidative stress as well as imbalance in plant water status (Razinger et al, 2008;López-Millán et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have evaluated uptake and translocation of Cd in rice at the molecular level (Takahashi et al 2011aFujiwara 2012, 2013). Heavy metal ATPase 3 (OsHMA3) participates in the sequestration of Cd into vacuoles in the root cells (Ueno et al 2010;Miyadate et al 2011).…”
Section: Introductionmentioning
confidence: 99%